Evaluation of Toxicity in the Combined Anticancer Potential of Pomegranate and Turmeric: A Comprehensive Study - Sujata M. Shendage, Khushi B. Ambre, Siddhi B. Wavhal, Nikita C. Wavhal, Aditya R. Suryawanshi, Shraddha N. Khandagale, Ashwini C. Satkar, Kiran C. Mahajan, Ganesh Y. Dama (South Eastern European Journal of Public Health, 2025)
Aim: The aim of this review is to investigate the potential of two natural substances, pomegranate (Punica granatum) and turmeric (Curcuma longa), in cancer therapy by evaluating their phytochemical composition, mechanisms of action, and safety profiles. Objective: The objective is to highlight the therapeutic properties of pomegranate and turmeric, specifically focusing on their ability to induce apoptosis, reduce cell proliferation, suppress angiogenesis and metastasis, and their anti-inflammatory, antioxidant, and anti-proliferative effects. Additionally, the review aims to assess their therapeutic synergy in preclinical studies and identify possible safety concerns, especially regarding drug interactions. Purpose: The purpose of this review is to provide a comprehensive understanding of the anticancer potential of pomegranate and turmeric and to explore their role in enhancing cancer treatment while minimizing toxicity. The review also aims to emphasize the need for further clinical studies to validate their efficacy and safety in diverse patient populations. Conclusion: The review concludes that pomegranate and turmeric show promising therapeutic efficacy in cancer treatment due to their bioactive compounds with antioxidant and anticancer properties. Their combined use may enhance therapeutic outcomes, but further clinical research is necessary to confirm their safety and efficacy in clinical settings. Caution is advised regarding potential drug interactions, particularly with cytochrome P450-dependent medications.